If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 74 + -6x = 21x + 23 Reorder the terms: 74 + -6x = 23 + 21x Solving 74 + -6x = 23 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 74 + -6x + -21x = 23 + 21x + -21x Combine like terms: -6x + -21x = -27x 74 + -27x = 23 + 21x + -21x Combine like terms: 21x + -21x = 0 74 + -27x = 23 + 0 74 + -27x = 23 Add '-74' to each side of the equation. 74 + -74 + -27x = 23 + -74 Combine like terms: 74 + -74 = 0 0 + -27x = 23 + -74 -27x = 23 + -74 Combine like terms: 23 + -74 = -51 -27x = -51 Divide each side by '-27'. x = 1.888888889 Simplifying x = 1.888888889
| 9+n-1-7n= | | 2b-8+4b-6b= | | 9-7x=45-14x | | -19-11a+a+16= | | -19-6x=5-10x | | 4y+23-y-6= | | 0x=6x | | 12-2(x+4)=15 | | 25-6x=3x+5 | | -6-7x=8x+24 | | 4m=27564 | | (2b+1)=11 | | 123-6x=2x+19 | | -29-3x=11-7x | | 4x^2-13x-12=0 | | (x+9)3= | | 5(2n-5)+4=14 | | 10m+7=3a+-11 | | 3x+14=86-6x | | h=-16t^2+400 | | 81-2x=34x+21 | | -3x-5+x=2x+7 | | 5X+36=15X-44 | | 7-7x=52-28x | | 12x-26=8x+2 | | -6x^2=-11x-10 | | x^2+8x+16=98.6 | | 3x-3=11x-27 | | 12(n-4)-5n=10n-3n | | 2x+30=10x-50 | | -4x+8-6x=2x-4 | | 2n+(2n+2)=8 |